Pelatihan Pemantapan Ms. Office Bagi Siswa/I Di Sma Swasta Yapim Simpang Kawat - Havid Syafwan; Pristiyanilicia Putri; Fauriatun Helmiah; Masitah Handayani (Smart Education, 2022)
Abstract: The role of information technology in the era of the Industrial Revolution 4.0 is currently very important and growing so rapidly. Moreover, in the school environment, especially for high school (SMA) students and their equivalent, those who are required to have special skills or skills are required. At Yapim Simpang Wire Private High School, the subject matter that discusses in more depth about information technology, especially the use of Microsoft Office applications on windows such as excel, word, and Powepoint, is still considered lacking. Even though the Microsoft office application is very useful for students in completing assignments at school and activities in their neighborhood. Therefore, this Microsoft office training is needed so that it can improve and strengthen the ability of students to operate this application in activities at school or their daily life. The purpose of this PKM activity is to improve and strengthen students' skills in operating computers, especially in Microsoft Office Word version 2016 such as using the basic tools they use in making paper assignments, managing writing such as font types, using margins, setting text in tables, file storage, print reports, and others.Keywords: training; information technology; microsoft office word 2016; yapim high school studentsAbstrak: Peranan teknologi informasi di zaman Revolusi Industri 4.0 saat ini sangat penting dan berkembang begitu pesatnya. Apalagi di lingkungan sekolah terutama bagi siswa-siswi Sekolah Menengah Atas (SMA) dan sederajatnya yang dituntut mesti memiliki skill atau keterampilan khusus. Pada SMA Swasta Yapim Simpang Kawat materi pelajaran yang membahas lebih mendalam mengenai teknologi informasi khususnya dalam penggunaan aplikasi Microsoft office pada windows seperti excel, word, dan power point masih dinilai kurang. Padahal aplikasi Microsoft office tersebut sangat berguna bagi para siswa-siswi dalam menyelesaikan tugas-tugas di sekolah maupun kegiatan dilingkungan tempat tinggal mereka. Oleh karena itu diperlukan pelatihan Microsoft office ini agar bisa meningkatkan dan memantapkan kemampuan siswa-siswi baik mengoperasikan aplikasi ini dalam aktifitas di Sekolah ataupun di keseharian mereka. Tujuan dari kegiatan PKM ini adalah dapat meningkatkan dan memantapkan keterampilan siswa siswi dalam pengoperasian komputer khususnya pada Microsoft Office Word versi 2016 seperti penggunaan tool-tool dasar yang mereka pakai dalam pembuatan tugas makalah, mengatur penulisan seperti jenis font, penggunaan margin, pengaturan teks dalam tabel, penyimpanan file, mencetak laporan dan lain-lainnya.Kata kunci: pelatihan; teknologi informasi; microsoft office word 2016; siswa-siswi sma yapim